2015
DOI: 10.1093/jac/dkv144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the efflux pump QepA2 combined with chromosomally mediated mechanisms on quinolone resistance and bacterial fitness inEscherichia coli: Table 1.

Abstract: The additive effect of chromosomally mediated fluoroquinolone resistance mechanisms and the qepA2 gene led to clinical levels of fluoroquinolone resistance. Under competitive conditions, the qepA2 gene had a biological cost in E. coli that was compensated for by the presence of an additional deletion in the marR gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
2
20
0
1
Order By: Relevance
“…Notably, other combinations of resistance determinants also show positive epistatic effects, although the observed effects are weaker. A similar positive epistatic effect was observed for chromosomal gyrA / parC mutations together with plasmid-mediated resistance determinants qepA 67 and aac(6’)Ib-cr . 52,75 However, experimental studies of combinations of gyrA and parC mutations with qnr genes showed discordant results.…”
Section: Discussionsupporting
confidence: 65%
“…Notably, other combinations of resistance determinants also show positive epistatic effects, although the observed effects are weaker. A similar positive epistatic effect was observed for chromosomal gyrA / parC mutations together with plasmid-mediated resistance determinants qepA 67 and aac(6’)Ib-cr . 52,75 However, experimental studies of combinations of gyrA and parC mutations with qnr genes showed discordant results.…”
Section: Discussionsupporting
confidence: 65%
“…The Ser83Ala gyrA mutation in E. coli was initially demonstrated to have no impact on the catalytic activity of the enzyme (Barnard and Maxwell, 2001 ) and subsequently both the Ser83Ala and Ser83Leu mutations were shown by multiple authors to confer a slight fitness advantage on the isolates (Komp Lindgren et al, 2005 ; Marcusson et al, 2009 ; Machuca et al, 2015 ; Huseby et al, 2017 ).…”
Section: The Energy Balance Associated With Individual Qrdr Mutationsmentioning
confidence: 99%
“…Bacterial resistance can occur by different mechanisms: alterations of the cell permeability, changes in the site of action leading to loss of susceptibility to the antibiotic mediated by the increment of the efflux pump activity and by enzymatic degradation of the antibiotic 12 - 14 . Regarding fluoroquinolones, its resistance depends essentially on three factors: the ability to select resistant mutants; the ability to reach concentrations that are able to avoid the resistance selection; and the ability to act against mutant bacteria generated during previous treatments with other fluoroquinolones 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%